PENERAPAN WHISTLEBLOWING SYSTEM DALAM MENCEGAH KECURANGAN DI PT XYZ LOMBOK - Baiq Agita Karenina Pratiwi; Elin Erlina Sasanti, Nungki Kartikasari (CV. ADIBA AISHA AMIRA, 2023)
In complex business world, fraud is a serious threat that can damage a company's reputation, affect financial performance, and harm stakeholders. Therefore, it is important to implement an effective whistleblowing system mechanism as a means of prevention and early detection of fraud at PT XYZ Lombok. The whistleblowing system is a system that manages the reporting of all activities that are contrary to laws, rules and ethical standards that are reported confidentially, anonymously and independently. The purpose of this study is to describe how the whistleblowing system is implemented at PT XYZ Lombok. This research was conducted using a qualitative method with a descriptive approach. Data collection by researchers is by way of observation, interviews and documentation. The informants in this study were general managers, marketing department managers, production department managers, accounting department managers and tax department managers. The results of the study show that PT XYZ Lombok has taken positive steps by implementing a whistleblowing system to prevent fraud. The implementation of the whistleblowing system has implemented almost all indicators in accordance with the violation reporting guidelines issued by the National Committee on Governance Policy and has a significant impact on preventing fraud. Although there are still obstacles in reporting fraud, measures in each department such as the use of confidants, the role of managers, anonymous reporting, and incentives for whistleblowers have provided effective solutions. This can be proven by the absence of fraud cases or indications of fraud cases that occurred at PT XYZ Lombok